POVERTY LEVEL AMONG FLUTED PUMPKIN FARMERS FACING HIGH PRODUCTION COSTS IN OGUN STATE, NIGERIA - Afodu, O. J.; Omotayo, P. M.; Akinboye, O. E.; Shobo, B.; Oyekale, O. O.; Awoyinka, R. I. (Nigerian Journal of Agriculture and Agricultural Technology, 2026)
The poverty situation in Nigeria has been eminent in the lives of smallholder farmers living in a hazardous environment with no access to basic services, good health, education and nutrition, coupled with low income and consumption levels. The study was carried out to investigate the poverty level of fluted pumpkin farmers in Ogun Sate, Nigeria. A multistage random sampling procedure was used in the selection of respondents for this study. The findings of the study shows that a significant majority (82.5%) of the vegetable farmers were living below the poverty line, which was set at 26,500 Naira per month. Mixed cropping technology was found to be significant at 1% level of probability with a negative coefficient of 0.117. The farming experience was also identified as a significant determinant affecting their poverty levels. The education of the farmers was also a significant factor that affect the poverty level of the vegetable farmers. The negative coefficient of 0.21 implies that a 1% increase in the farmers’ education will lead 21% decrease in their poverty level. Poverty alleviation can be achieved among fluted pumpkin farmers in the study area by putting into consideration the various techniques of vegetables cultivation and education of the farmers.